Is the criminal justice system blind to race and ethnicity?: The case of fatal work accidents in the construction industry: Is the criminal justice system blind to race and ethnicity - shoham, efrat; Nictora, Eitan (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2019)
Despite growing media and public interest in recent years in the issue of fatal work accidents in the construction industry, there in fact has been an upswing in the number of fatalities. The construction industry is a dangerous industry for workers, and about half of the fatal work accidents in Israel take place there. This study was designed to examine how the law enforcement system handles cases of fatal work accidents, where most of the workers are foreign workers. The article examines whether there is a difference in the criminal procedures between work accidents and road accidents, which are not identified with a particular demographic sector. The study findings showed that there is a significant link between the type of fatal accident and the identity of the victim, and the decisions made during the criminal proceedings for a fatal work accident as compared to a fatal road accident. The findings partially correspond with the assumptions of the Marxist structural school of victimology, which sees a relationship between the victim’s social status and the way the criminal justice system handles the case. Although based on a relatively small sample, these findings indicate that there is a need to substantially strengthen and regulate the investigative and criminal aspects of the treatment of fatal work accidents in the construction industry.